Impact of Integrated Financial Management Information System on Internal Audit Practice. A Case Study of the Ministry of Finance in Juba, South Sudan - Nhial, Awur Majur; Shiku, Ulayi Owen; Jacqueline Siwale , Jacqueline Siwale (International Journal of Finance, 2025)
Purpose: This study investigates how the implementation of Integrated Financial Management Information Systems (IFMIS) influences internal audit practices at the Ministry of Finance in Juba, South Sudan. It aims to assess IFMIS's impact on governance and financial accountability, particularly in a developing country like South Sudan, which struggles to provide accurate and transparent financial records. Methodology: The study employed a descriptive method, surveying 86 respondents selected by multistage selection from a target population of 150. Preliminary findings reveal that IFMIS significantly affects internal audit practices, with key correlations found between internal control systems (p = 0.003), organizational accountability (p = 0.011), and financial reporting systems (p = 0.024). However, no significant link was found between cash management, budgeting systems, and internal audits (p = 0.092). Findings: The research suggests that improving government financial transaction recording and processing facilitates better access to reliable financial data, enhancing transparency and accountability. The study concludes that strengthening cash management, expanding the scope of financial reporting, and improving internal control systems are essential for effective IFMIS integration in South Sudan's public finance management Unique Contribution to Theory, Policy and Practice: The research focused on public sector management in South Sudan, emphasizing the role of the Integrated Financial Management Information System (IFMIS) in enhancing internal audits, transparency, and accountability. It proved beneficial to the Ministry of Finance and Planning, improved taxpayer morale, and encouraged greater private sector investment. Additionally, the study provided a valuable framework for future research on financial management reforms in developing countries (Aguto & Akol, 2018).